COUNTERGRADIENT VARIATION IN GROWTH OF BARB (Barbonymus balleroides Val. 1842) DOMESTICATED AT DIFFERENT ALTITUDES - Jojo Subagja; Vitas Atmadi Prakoso; Otong Zenal Arifin; Endang Haris Suhud (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2018)
Barb (Barbonymus balleroides Val. 1842) is one of the native species found in many rivers of Asian countries, including Indonesia. This species had higher commercial value compared with other fish species popular among consumers. In terms of supporting its domestication, information regarding the optimal aquaculture system of the fish is needed, one of which is its rearing location. Currently, there is limited information on rearing the fish at different locations with different altitude. This research aimed to obtain the growth of barb fingerlings reared in three locations with different altitudes. The study was conducted in the ponds located at Cijengkol area (ASL<200 m), Maleber (200 m<ASL<400 m), and Ciherang (ASL>400 m), West Java. Fingerlings of domesticated barb (total length 4.48 ± 0.10 cm; weight 0.95 ± 0.06 g) were stocked in three fixed net cages (size 2 m × 2 m × 1 m) in a pond (40 m × 20 m) at each location. Fish were fed with commercial feed (30% protein) of 5% biomass three times per day during 120 days of rearing. Water quality parameters observed were temperature, dissolved oxygen, and pH. Measured parameters were length gain, weight gain, specific growth rate, average daily growth, biomass gain, feed conversion ratio, and survival rate. The results showed that the fish reared in Maleber showed the best growth and feed conversion ratio compared to other locations (P<0.05). Meanwhile, no significant differences were found on the survival rate within all treatments. The growth of barb fingerlings is more optimal if reared in midland areas which have suitable temperature ranges for their growth.